Changes In the Training of Scientific and Academic-Pedagogical Personnel In Uzbekistan During the Early Years of Independence - Qushmirzayevich, Khoshimov (Indonesian Journal Publisher, 2025)
This article discusses the reforms carried out by the state and their outcomes in the fields of training scientific and academic-pedagogical personnel, as well as postgraduate education, during the initial years of Uzbekistan’s independence (1992–1996). In particular, the article analyzes the changes that occurred as a result of developing and effectively implementing action plans aimed at enhancing the scientific potential of higher education institutions under the Ministry of Higher and Secondary Specialized Education of the Republic, as well as addressing issues in the fields of training scientific and academic-pedagogical personnel.